Hubungan Antara Paritas Dengan Kejadian Rupture Perineum Pada Ibu Bersalin Di BPS Hj. Farida Hajri Amd. Keb. Surabaya - Dewi bidan; Fahrun Nur Rasyid; Umi Ma'rifah; Nur Mukarromah (Sinar : Jurnal Kebidanan, 2022)
Objective: Analyzing the relationship between maternal parity and the incidence of perineal ruptureMethods: This research used analytic as design by cross sectional to analyzed the relation between parity and rupture perineum. This research was done at BPS Hj.Farida Hajri AMd.Keb on July 2010. Samples were taken by simple random sampling amount 28 respondents. Data was collected by observation sheet then analyzed by SPSS 17 Chi-Square Test.Result: The result of this research showed Ï 0.002 lower than Î± 0.05. H0 was declined which also indicated that there was relation between parity and rupture perineum incident. Conclusion: Higher parity, higher rupture perineum incident to puerperal mother.